Studi Korelasi Antara Vocabulary Mastery, Grammar MasteryDan Minat Belajar Dengan Prestasi Belajar Matematika Pada Siswa Kelas Internasional Di Madrasah Tsanawiyah Pondok Pesantren Modern Islam Assalam Surakarta Tahun Pelajaran 2014/2015 - Ferdiana, Wury; , Prof. Dr. Budi Murtiyasa, M.Kom (2015)
Development of globalization in education is increasing, as the development of technology. Many schools have started to compete in the arena. International school using English as an introduction to this study aimed to determine the relationship between vocabulary mastery, mastery of grammar and student interest in learning achievement in the subject numbers sequence and series.This research is a quantitative survey research method. The study subjects were students of class IX International 1 mts PPMI Assalam Surakarta totaling 30 students. Methods of data collection using tests and questionnaire. Method of data analysis is the statistical correlation and regression. The results showed: (1) there is a correlation between vocabulary mastery and learning achievement, with a correlation index of 0.43, (2) there is no correlation between mastery of grammar and mathematics achievement, (3) there is a correlation between learning and learning achievement mathematical correlation with the index of 0.38, (4) there is no correlation between vocabulary mastery, mastery of grammar and interest in learning the mathematics achievement. The relative contribution of vocabulary mastery 57.71%, while the interest in learning is 42.29%. Effective contribution given vocabulary is 16.56%, while the interest in learning is 12.13%.